Exploring the ecology of invertebrate communities in subterranean habitats of a subtropical karst - Melo, Leandro Mata da Rocha (2025)
Subterranean environments represent locations where biodiversity is still underexplored, with vast expanses yet to be mapped and unknown species. These cave ecosystems harbor a wealth of species that have specialized to the unique conditions of these environments, such as the tendency for environmental stability and resource scarcity. However, these environments are under increasing threat due to human activities such as deforestation, agriculture, mining, and urbanization, which compromise the integrity of subterranean habitats. In the state of Paraná, which stands out as one of the leaders in deforestation in Brazil, cave environments face even more acute challenges. Deforestation results in a decrease in the supply of resources, such as organic matter and nutrients, to subterranean systems, exacerbating their natural oligotrophic characteristics. This resource depletion has a direct impact on cave biodiversity, leading to species loss. Additionally, anthropogenic activities can also cause direct physical damage to caves, whether through road construction, mining, or pollution. Thus, this study aimed to investigate the variables that influence the composition and richness of invertebrates in caves in Paraná, as well as to conduct a systematic review to understand which variables are being tested in studies on the topic and to identify knowledge gaps. We updated the troglobitic fauna in the northern region of Paraná and identified priority caves for conservation in the study area. We found that both temperature and shelter diversity influence fauna composition at a mesoscale, while the distance from the cave entrance and the distance between caves are significant determinants of fauna at a microscale. We identified a total of 28 troglobitic species and 9 caves as of extreme conservation priority. The review revealed that various variables have been tested in the field of cave community ecology, but knowledge gaps still remain, such as the study of ecological relationships in cave environments, ecological succession, biotic interactions, functional ecology, and metacommunities. By identifying the environmental variables that structure cave communities, we can direct efforts to mitigate negative impacts and promote more effective conservation practices. Additionally, by identifying priority caves for conservation, we can concentrate resources and efforts where they are most needed, maximizing the impact of protection measures.